2020
DOI: 10.1007/s40544-019-0336-9
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of TiO2/gC3N4 nanoadditive to boost oxidative properties of vegetable oil for tribological application

Abstract: The emergence of vegetable oil as a promising alternative lubricant in the tribological application space has fueled research for making these oils as useful as mineral oils. Tribological modification of vegetable oil by the addition of TiO 2 /gC 3 N 4 nanocomposite (as a nanoadditive) was studied here. The dispersion of the nanoadditive in the vegetable oil showed good oil dispersion stability without the addition of any surfactant. The tribological studies were conducted in a four-ball tester using ASTM stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The nanoscale polishing effect mechanism is occurring on the sliding surface, leading to an abrasive wear phenomenon. The presence of metal oxides and carbon nitrides in the nano-oil significantly contributes to the reduction in tribological properties . Kao and Lin achieved 18, 80, and 50% reductions in COF, wear scar depth, and surface roughness, respectively, by dispersing TiO 2 in the paraffin oil .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoscale polishing effect mechanism is occurring on the sliding surface, leading to an abrasive wear phenomenon. The presence of metal oxides and carbon nitrides in the nano-oil significantly contributes to the reduction in tribological properties . Kao and Lin achieved 18, 80, and 50% reductions in COF, wear scar depth, and surface roughness, respectively, by dispersing TiO 2 in the paraffin oil .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of metal oxides and carbon nitrides in the nano-oil significantly contributes to the reduction in tribological properties. 33 Kao and Lin achieved 18, 80, and 50% reductions in COF, wear scar depth, and surface roughness, respectively, by dispersing TiO 2 in the paraffin oil. 7 Birleanu et al got a 55% reduction in COF by adding TiO 2 NPs in the 10W-30 engine oil.…”
Section: N-ac-tio 2 -Eo Nano-oilsmentioning
confidence: 99%
“…The spectra of sample M3 showed the appearance of intense peaks at 2915 cm -1 and 2848 cm -1 representing the C-H and C-O bonds respectively. The characteristic peaks at 1696 cm -1 and 1576 cm -1 were assigned to the symmetric υ(COO-) symm and asymmetric υ(COO-) asymm carboxylate group stretching band [18]. This signifies the surface modification of MoS 2 using Lithium Stearate.…”
Section: Ftir Analysismentioning
confidence: 90%
“…At present, scientists have made a lot of efforts, and many related research results have been reported. Vegetable oil has been widely studied as green lubricant due to the good friction properties, biodegradability and non-toxicity, and many researchers have also used various methods to further improve the properties of vegetable oils, such as oxidation stability and tribological properties [13][14][15]. For example, Kerni et al, investigated the tribological properties of olive oil in boundary and mixed lubrication regimes.…”
Section: Introductionmentioning
confidence: 99%